On the observed results of the intensity and the polarization of narrow-band auroral hiss emissions - Nishino, Masanori; Tanaka, Yoshihito; Iwai, Akira; Kamada, Tetsuo; Hirasawa, Takeo (1983)
P(論文) Results of intensity and polarization measurements of narrow-band auroral hiss observed simultaneously with the direction finding (DF) observations at Syowa Station, Antarctica, are compared with results of the full-wave calculation in a realistic ionospheric model. The ratios of the 8kHz hiss intensity observed at Syowa to that at Mizuho Station (about 270km distant from Syowa in the geomagnetic south direction) depend on the propagation distance from the exit regions at the height of the lower edge of the ionosphere to the two ground stations. However, the observed ratios (SY/MI) are 2-3 dB higher than the corresponding theoretical values. The disagreement is discussed as regards to the effects of the wave polarization and the ground conductivity at the observing site on the received wave intensity. The distribution of R/L (R-to L-handed polarized component) values of the narrow-band auroral hiss observed at Syowa with incident angles indicates a similar tendency to the R/L values for the limiting polarization by full-wave calculation, but the observed values are smaller than the calculated ones. The disagreement seems to be caused by the low accuracy of DF at small incident angles, and by the disturbance from strong VLF atmospherics. departmental bulletin paper